Associative Increases in Amyotrophic Lateral Sclerosis Survival Duration With Non-invasive Ventilation Initiation and Usage Protocols - Khamankar, Nishad; Coan, Grant; Weaver, Barry; Mitchell, Cassie S. (Frontiers in Neurology, 2018)
Objective: It is hypothesized earlier non-invasive (NIV) ventilation benefits Amyotrophic Lateral Sclerosis (ALS) patients. NIV typically consists of the removable positive airway pressure (Bi-PAP) for adjunctive respiratory support and/or the cough assist intervention for secretion clearance. Historical international standards and current USA medical insurance standards often delay NIV until percent predicted forced vital capacity (FVC %predict) is <50. We identify the optimal point for Bi-PAP initiation and the synergistic benefit of daily use of both Bi-PAP and cough assist on associative increases in survival duration. Methods: Study population consisted of a retrospective ALS cohort (Emory University, Atlanta, GA, USA). Analysis included 474 patients (403 Bi-PAP users, 71 non-users). Survival duration (time elapsed from baseline onset until death) is compared on the basis of Bi-PAP initiation threshold (FVC %predict); daily Bi-PAP usage protocol (hours/day); daily cough assist usage (users or non-users); ALS onset type; ALSFRS-R score; and time elapsed from baseline onset until Bi-PAP initiation using Kruskal-Wallis one-way analysis of variance and Kaplan Meier. Results: Bi-PAP users’ median survival (21.03 months, IQR=23.97, N=403) is significantly longer (p<0.001) than non-users (13.84 months, IQR=11.97, N=71). Survival consistently increases (p<0.01) with FVC %predict Bi-PAP initiation threshold: <50% (20.3 months); 50% (23.60 months); 80% (25.36 months). Bi-PAP usage >8 hours/day (23.20 months) or any daily Bi-PAP usage with cough assist (25.73 months) significantly (p<<0.001) extends survival compared to Bi-PAP alone (15.0 months). Cough assist without Bi-PAP has insignificant impact (14.17 months) over no intervention (13.68 months). Except for bulbar onset Bi-PAP users, higher ALSFRS-R total scores at Bi-PAP initiation significantly correlate with higher initiation FVC %predict and longer survival duration. Time elapsed since ALS onset is not a good predictor of when NIV should be initiated. Conclusions: The “optimized” NIV protocol (Bi-PAP initiation while FVC %predict 80, Bi-PAP usage >8 hours/day, daily cough assist usage) has a 30.8 month survival median, which is double that of a “standard” NIV protocol (initiation FVC %predict <50, usage >4 hours/day, no cough assist). Earlier access to Bi-PAP and cough assist, prior to precipitous respiratory decline, is needed to maximize NIV synergy and associative survival benefit.